Synthesis, anticancer evaluation, and molecular docking studies of thiazolyl-pyrazoline derivatives. (15th January 2023) - Hosseini Nasab, Narges; Azimian, Fereshteh; Shim, Rok Su; Eom, Young Seok; Shah, Fahad Hassan; Kim, Song Ja
Graphical abstract: Highlights: A series of thiazolyl-pyrazoline derivatives (7a -k ) were synthesized and characterized. The compounds were evaluated as anti-proliferative agents against A549 and A375. Potent compounds were tested for cycloxygenase-2 and matrix metalloproteinase expression. Molecular docking studies were carried out to investigate the binding mode of potent compounds with COX-2. Abstract: The molecular hybridization of thiazole and pyrazoline heterocyclic structures with diverse activities appears to be an interesting strategy for developing new anticancer compounds. This study presents the synthesis of eleven new thiazolyl-pyrazoline derivatives (7a -k ) and the evaluation of their in-vitro anti-proliferative activities against human lung carcinoma (A549) and human melanoma cancer (A375) cell lines through MTT assay. In comparison to the positive reference drug erlotinib (IC50 = 34.16 µM in A549 and IC50 = 25.85 µM in A375), four compounds (7e, 7h, 7j, and 7k ) were identified as the most active against both cell lines (especially compound 7k with IC50 = 20.28 µM in A549 and 16.08 µM in A375). Additionally, these potent compounds were selected to be investigated for their anti-metastasis and anti-inflammatory properties via inhibition of the expression of matrix metalloproteinase 2, 9 (MMP-2, 9) and cyclooxygenase 2 (COX-2). In A549 cells, upon exposure to compounds 7e and 7j, COX-2 expression is decreased, whereas compounds 7e, 7j, and 7k reduced COX-2 expression in A375 cell lines. Molecular docking studies were carried out to show the possible interactions of synthesized compounds with the predicted active site of the COX-2 protein. The results revealed that compounds 7e and 7j can bind well to the active site of COX-2 protein. Collectively, compounds 7e, 7j, and 7k are all promising candidates for further research towards the development of novel anticancer agents.